Relevance y level of application de las management competencies in nursing (2013)
ABSTRACT: The study sought to identify the relevance and level of application of the main management competencies in nursing. Methodology. Study contains qualitative and quantitative components with a descriptive approach. We took as categories of the study the relevance and application of management competencies and curricular strategies for their formation. A survey was applied to a convenience sampling of 140 individuals from the nursing faculties involved and from different levels of healthcare in the city of Medellín and its Metropolitan Area; lastly, a semi-structured interview was made of six experts from the university educational sector in Medellín. Results. The most relevant generic competencies were: leadership (81.4%), team work (75.0%), effective communication (55.7%); while the specific competencies highlighted quality management of personnel and care. Innovation and creativity competencies (19.3%), strategic thought (17.1%), and adaptability or flexibility (10.0%) obtained lower frequencies. The level of application of specific competencies, according to components of strategic management, programs and projects, quality, human talent, and caretaking of individuals was above 90%. Conclusion. The management competencies identified were relevant and of high applicability for the people consulted. The complexity paradigm as central axis may contribute to their formation.